2018
DOI: 10.1007/s00105-018-4134-5
|View full text |Cite
|
Sign up to set email alerts
|

Igelpilze in einer Münchner Hautarztpraxis

Abstract: Patient 1: After contact to a central European hedgehog (Erinaceus europaeus), a 50-year-old female with atopy developed erythrosquamous tinea manus on the thumb and thenar eminence of the right hand. The patient had previously been scalded by hot steam at the affected site. The zoophilic dermatophyte Trichophyton erinacei could be cultured from the hedgehog as well as from scrapings from the woman's skin. Antifungal treatment of the hedgehog was initiated using 2 weekly cycles of itraconazole solution (0.1 ml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 23 publications
0
14
0
7
Order By: Relevance
“…However, it is also very possible that the infection of dogs with N. persicolor could occur through contact with soil. The origin of T. erinacei in a patient could be traced to contact with a hedgehog [16], as was the case for several cases of this emerging dermatophyte species in Spain and Germany [29][30][31][32].…”
Section: Discussionmentioning
confidence: 95%
“…However, it is also very possible that the infection of dogs with N. persicolor could occur through contact with soil. The origin of T. erinacei in a patient could be traced to contact with a hedgehog [16], as was the case for several cases of this emerging dermatophyte species in Spain and Germany [29][30][31][32].…”
Section: Discussionmentioning
confidence: 95%
“…Abbreviations: SQLE, squalene epoxidase; ITS, internal transcribed spacer; TEF1-α, translation elongation factor 1-α; MIC, minimum inhibitory concentration; NCBI, National Center for Biotechnology Information, Bethesda, Maryland; DSM, Deutsche Sammlung von Mikroorganismen und Zellkulturen (German Collection of Microorganisms and Cell Cultures), Braunschweig, Germany; f, female; m, male. For confirmation of the suspected dermatophyte species, Sanger sequencing of the ITS regions of rDNA genes (mainly the regions ITS 1, 5.8 S rRNA, ITS 2) and TEF1-α gene was performed for all isolates [6][7][8][9]. This required PCR amplification of a ∼900 bp DNA fragment using universal primers that bind to flanking pan-fungal sequence regions: V9G (5'-TTACGTCCCTGCCCTTTGTA-3') and LS266 (5'-GCATTCCCAAACAACTCGACTC-3').…”
Section: Pcr-elisa For Molecular Identification Of Dermatophytesmentioning
confidence: 99%
“…T. cf. erinacei strains seem to be quite rare but have been isolated in Africa, Europe, and North America during the past few decades [19,34]. Screening of 412 European hedgehogs at a wildlife center in Paris did not yield any strains of this genotype [35].…”
Section: Discussionmentioning
confidence: 93%
“…They isolated several strains from European hedgehogs of the divergent T. cf. erinacei genotype [34]. Kargl et al concluded that the divergent ITS genotype of the T. cf.…”
Section: Discussionmentioning
confidence: 99%